PENGARUH DAYA TARIK WISATA, KUNJUNGAN WISATAWAN DAN LAMA TINGGAL WISATAWAN TERHADAP PAD KABUPATEN/KOTA PROVINSI BALI - Sari, Ayu Rai Wulan Puspita; Dewi, Made Heny Urmila (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
The purpose this research is to analyze effect Tourist Attractions, Tourist Visits, and Length of Stay Tourists on the Locally-Generated Revenue in Regency/City of Bali Province in 2010-2020. This research was conducted in Regency/City of Bali Province. The data that used in this research are secondary data that came from relevant agencies, so that the number of observations is 99 observations. The analysis technique used is panel data regression analysis and multiple linear regression analysis. The results of this research conclude that simultaneously Tourist Attractions, Tourist Visits and Length Of Stay Tourists have a significant effect to Locally-Generated Revenue in the Regency/City of Bali Province, partially the Tourist Attractions has not any significant to Locally-Generated Revenue, Tourist Visits have a significant  positive effect to Locally-Generated Revenue, while the Length of Stay Tourists has a not effect to Locally-Generated Revenue, and the most dominant influence to Locally-Generated Revenue is Tourist Visits.